THU0596 DIAGNOSTIC VALUE OF ULTRASOUND AND DUAL ENERGY COMPUTED TOMOGRAPHYTO ACHIEVE ACR-EULAR GOUT CLASSIFICATION CRITERIA IN REAL LIFE CLINICAL PRACTICE. (June 2019) - Ramon, André; Schmitt, Marie; Ne, Romaric; Berthod, Pierre Emmanuel; Devilliers, Hervé; Maillefert, Jean Francis; Ornetti, Paul
Abstract : Background: 2015 ACR/EULAR gout classification criteria (1) include ultrasound with double contour (DC) sign as key ultrasound features and dual energy computed tomography (DECT) with evidence of urate deposition. The positivity of either DECT or ultrasound allows 4 points in addition to others clinical and biological criteria to classify as gout is ≥8/23. However, in routine care, the imaging modality that should be promoted remains unclear between ultrasound or DECT. Objectives: To validate a possible diagnostic algorithm for the clinical use of DECT and ultrasound in suspected gouty arthritis. Methods: We conducted a single-center prospective study in the Rheumatology Department of Dijon University Hospital from july 2016 to december 2018, including all patients hospitalized for suspected gouty arthritis. Each patient received joint aspiration if possible, an ultrasound assessment (DC sign and/or tophus) and DECT scanning of symptomatic joints. All these examinations were performed blind of the clinical data and results of joint aspiration. The gold standard used for this study was the 2015 ACR/EULAR gout classification criteria. We have established two scenarios derived from the algorithm proposed by Nötzel et al (2): in scenario A, the DECT was performed first followed by ultrasound; in scenario B, ultrasound was performed first followed by DECT. Test performance such as sensitivity, specificity, positive and negative predictive value (PPV, NPV)) were calculated for each imaging techniques. Statistical analysis was performed by SAS/STAT software and Macnemar test was used to compare the two scenarios. Results: 40 consecutive patients were included. 3 patients had a score ≥8 from clinical data alone and classified as gout. The remaining 37 patients were included according to the two scenarios. In scenario A, 9/37 patients had a DECT positive with urate deposition leading to the diagnostic of gout with an ACR/EULAR score ≥ 8. 7/37 patients had a positive DECT without reaching ACR/EULAR treshold (< 8). 21/37 patients had a negative DECT. The ultrasound study of these 28 patients did not find any sign of gout (DC sign). In scenario B, 6/37 patients had a DC sign and an ACR/EULAR score ≥ 8. 1/37 patient had a DC sign but an ACR/EULAR score < 8. 30/37 patients had no ultrasound DC sign. DECT in these 31 patients revealed sodium urate deposits in 3/31 patients, leading to a score ≥8. DECT was positive in 7/31 patients with an ACR/EULAR score < 8. The comparison between the 2 scenarios did not find a significant difference (p = 0.250). For the DC sign, sensitivity = 66%, specificity = 96%, PPV = 89% and NPV = 87%. For the presence of DC sign and/or tophus, the values were 91%, 96%, 91%, 96% respectively. For DECT, sensitivity =100%, specificity = 75%, PPV = 63%, NPV = 100%. Conclusion: Our results confirm that ultrasound (DC sign alone) and DECT have similar diagnostic performance in gouty arthritis in routine care. It seems clinically relevant to propose the ultrasound as first imaging modality considering both the presence of the DC sign and/or ultrasound tophus (not included in ACR-EULAR criteria). It significantly improves the sensitivity of ultrasound while maintaining its PPV, with less false positive patients compared to DECT. References: [1] Neogi T, Jansen TLTA, Dalbeth N, et al. 2015Gout Classification Criteria: an American College of Rheumatology/European League Against Rheumatism collaborative initiative. Arthritis & Rheumatology. 2015; 67:2557–68. [2] Nötzel A, Hermann K-G, Feist E, et al. Diagnostic accuracy of dual-energy computed tomography and joint aspiration: a prospective study in patients with suspected gouty arthritis. Clin Exp Rheumatol. 2018; 36 :1061–7. Disclosure of Interests: None declared